A multiband patch antenna with embedded square split ring resonators in non-Homogeneous substrate - Shailesh M. Rao; Prabhugoud I. Basarkod (Bulletin of Electrical Engineering and Informatics, 2021)
The authors have attempted to influence an embedded square split ring resonator (SSRR) response in a stacked non-homogeneous substrate to demonstrate a quad-band antenna. The purpose is to produce multiband operations of a microstrip patch antenna. The highlighted factor is the effect of embedding an SSRR and the differing relative permittivity of the substrate on the side length of the SSRR. The analysis shows that a non-homogeneous dual substrate patch produces multiple bands compared to a single substrate patch antenna without any parameter change. A dual substrate antenna fabricated using FR4 and Rogers RT/Duroid 5880 copper clad sheets with a dimension of 85.6x54x0.908 mm3 (0.314λ0x0.198λ0x0.003λ0). The antenna resonates at 1.1, 2.45, 3.65 and 5.25 GHz in the L-, S- and C-bands. It is possible to employ the patch antenna in WLAN (dual-band) and WiMAX applications and suitable for mobile broadcast service at 1.1 GHz. The authors compare the simulated and measured results of a prototype in the article. The maximum measured gain is 5.48 dBi at 1.1 GHz and 4.025 dBi at 3.65 GHz. The measured bandwidth is 60 MHz (1.2%) at 5.25 GHz.